Case report of cutaneous protothecosis caused by Prototheca wickerhamii designated as genotype 2 and current status of human protothecosis in Japan. Issue 1 (16th August 2017) - Inoue, Maki; Miyashita, Azusa; Noguchi, Hiromitsu; Hirose, Noriyuki; Nishimura, Kazuko; Masuda, Michiaki; Ihn, Hironobu
Abstract: An 85‐year‐old Japanese woman presented with infiltrative erythema and ulceration on the extensor surface of her right forearm. Direct microscopic examination demonstrated spherical and morula‐like sporangia, while histopathology revealed numerous microorganisms with a mulberry‐like appearance in the dermis. Staining of the microorganisms also showed mulberry‐like sporangia that resembled the spokes of a wheel. The isolated yeast‐like microorganism had been identified as Prototheca wickerhamii genotype 2 in another independent study on the basis of its morphological, biochemical and genetic analysis. This case of protothecosis was recorded in Kyushu, Japan, and oral treatment with itraconazole 200 mg/day for 2 months was effective. Herein, we also summarize and analyze 39 cases of human protothecosis reported in Japan since the first record in 1983.